Descriptions of new species and new records of Sericini from Southern India and Nagaland (Coleoptera: Scarabaeidae: Sericinae) - Sreedevi, Kolla; Ahrens, Dirk (Zootaxa, 2025)
Six new species of Sericini (Coleoptera: Scarabaeidae: Sericinae) are described from India: Maladera silviae Sreedevi & Ahrens, sp. nov., M. judithae Sreedevi & Ahrens, sp. nov., M. thandigudiensis Sreedevi & Ahrens, sp. nov., M. (Hemiserica) subinaequalis Sreedevi & Ahrens, sp. nov., Neoserica berlineri Sreedevi & Ahrens, sp. nov., and Selaserica peechi Sreedevi & Ahrens, sp. nov. For the new species, differential diagnoses and illustrations of male genitalia and habitus are provided. This paper also presents new locality records of 29 species from India, including one first country and 11 new state records.